Kepemimpinan Khalifah Umar Bin Khattab dalam Perubahan Sosial dan Pengembangan Pendidikan Islam pada Masa Pemerintahannya - Husnul Amaliyah; Ani Marlia; Nadila Afrilia; Rangga Apri Sandi; Lilis Permita Sari (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The governance of Caliph Umar ibn al-Khattab was crucial in the history of Islam, leading to considerable social reforms and advancements in Islamic education. As the second caliph, Umar was recognized for his innovative approaches that reinforced the social and educational foundations of the Muslim community. On the social front, he implemented welfare programs through the Bayt al-Mal, allocated zakat to assist those in need, and set minimum living standards to avert starvation. In terms of education, Umar sent scholars throughout Islamic regions to impart knowledge of the Qur'an and Islamic principles, and he founded mosques as hubs of learning. Instructional approaches like halaqah and talaqi were utilized, with educators receiving salaries from the Bayt al-Mal.  These initiatives demonstrate that Umar was committed not just to territorial growth but also to the intellectual and ethical upliftment of society. This research intends to examine the significant impact of Umar ibn al-Khattab on social change and the creation of a strong Islamic educational framework during the early days of the caliphate.